Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Konsumen Menggunakan Jasa Rental Alat Outdoor Astrajingga - Acep Miftah Fauzi; Ari Arisman; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of service quality and product quality on consumer satisfaction using Astrajingga outdoor equipment rental services (Survey of Astrajingga Store Consumers). The method used in this study is causality through a survey approach. With a research sample of 100 Astrajingga Store Consumers. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that service quality has a very good rating classification, product quality has a very good rating classification, while consumer satisfaction has a good rating classification for Astrajingga Store Consumers in Tasikmalaya City. Simultaneously service quality and product quality have a significant influence on customer satisfaction. Partially, service quality has a significant influence on consumer satisfaction and product quality has a significant influence on consumer satisfaction using Astrajingga Outdoor Equipment Rental Services.